2011
DOI: 10.1007/s11239-011-0637-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of colchicine compared with placebo on high sensitivity C-reactive protein in patients with acute coronary syndrome or acute stroke: a pilot randomized controlled trial

Abstract: There is a need for more effective therapies to reduce morbidity and mortality from cardiovascular disease. Inflammation plays a central role in the pathogenesis of atherosclerosis but no randomized studies have evaluated anti-inflammatory therapy in patients with acute coronary or cerebrovascular disease. We performed a pilot randomized controlled trial comparing the effect of colchicine 1 mg per day with placebo on high sensitivity C-reactive protein (CRP) levels and platelet function in 80 patients with acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 14 publications
2
105
0
4
Order By: Relevance
“…Based on our study, this putative mechanism of action may not translate into functional effects on platelet aggregation in the setting of therapeutic oral colchicine administration. One pilot study did evaluate the effect of oral colchicine 1 mg per day in 80 patients with acute coronary syndrome or acute ischemic stroke on a background of aspirin therapy, 85% of which were on dual anti-platelet therapy with clopidogrel [16]. In a subgroup of 49 patients with platelet aggregation measured, there was no noted difference in platelet aggregation in response to ADP, arachadonic acid, or collagen [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our study, this putative mechanism of action may not translate into functional effects on platelet aggregation in the setting of therapeutic oral colchicine administration. One pilot study did evaluate the effect of oral colchicine 1 mg per day in 80 patients with acute coronary syndrome or acute ischemic stroke on a background of aspirin therapy, 85% of which were on dual anti-platelet therapy with clopidogrel [16]. In a subgroup of 49 patients with platelet aggregation measured, there was no noted difference in platelet aggregation in response to ADP, arachadonic acid, or collagen [16].…”
Section: Discussionmentioning
confidence: 99%
“…One pilot study did evaluate the effect of oral colchicine 1 mg per day in 80 patients with acute coronary syndrome or acute ischemic stroke on a background of aspirin therapy, 85% of which were on dual anti-platelet therapy with clopidogrel [16]. In a subgroup of 49 patients with platelet aggregation measured, there was no noted difference in platelet aggregation in response to ADP, arachadonic acid, or collagen [16]. Likewise, another study demonstrated no difference in mean platelet volume, a marker of platelet activity based on size, between patients with familial mediterranean fever on colchicine and age- and sex-matched healthy subjects [1718].…”
Section: Discussionmentioning
confidence: 99%
“…Nidorf and Thompson reported that, in patients with stable coronary artery disease and elevated CRP, 0.5 mg colchicine twice daily resulted in a 60% decrease in CRP levels at 4 weeks, compared with control patients 45 . On the other hand, Raju, et al found no lowering of CRP in patients receiving 30 days of colchicine, 1 mg daily, after MI or stroke 46 . Given the relative safety of colchicine, as well as its activity against cells implicated in plaque formation, rupture, and thrombosis, it would be desirable to know whether colchicine could be of benefit in preventing CV events.…”
mentioning
confidence: 97%
“…Low-dose colchicine (0.5 mg twice daily) was associated with a relative 60% reduction in hs-CRP levels independent of aspirin and statin use. On the contrary, a small pilot study with 80 patients with ACS or acute ischaemic stroke showed no difference in hsCRP levels or platelet aggregation at 30 days between colchicine therapy (1 mg/day) and placebo 49. However, this study was inadequate in assessing the clinical benefit of colchicine given small sample size and was not specific for ACS.…”
Section: Colchicine In Cardiac Diseasesmentioning
confidence: 76%